2019
DOI: 10.1093/afraf/ady068
|View full text |Cite
|
Sign up to set email alerts
|

The politics of cholera, crisis and citizenship in urban Zimbabwe: ‘People were dying like flies’

Abstract: Zimbabwe’s catastrophic cholera outbreak of 2008/09 resulted in an unprecedented 100,000 cases and nearly 5,000 deaths. In the aftermath of the epidemic, questions of suffering and death and of rescue, relief, and rehabilitation have persisted in on-going processes of meaning-making through which people come to terms with the epidemic as a ‘man-made’ disaster. Based on extensive fieldwork, I examine the views of residents in Harare’s high-density townships that were epicentres of the disease. I argue that chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 2 publications
1
17
0
3
Order By: Relevance
“…This household-level crisis was characterised by a sudden but extended loss of income, increased hunger, isolation from social support systems, feeling unable to provide for family members, and feeling that their exposure to cholera may tarnish their social standing in the long term. These lived experiences of cholera are consistent with existing, but limited, literature from other settings where cholera outbreaks occur during complex crises or within fragile states and among populations with high levels of poverty [ 40 , 41 ]. Our study found that exposure to cholera decreased the household’s access to food and made it hard to prioritise handwashing due to a reduced ability to access water purchase soap in the wake of their illness.…”
Section: Discussionsupporting
confidence: 82%
“…This household-level crisis was characterised by a sudden but extended loss of income, increased hunger, isolation from social support systems, feeling unable to provide for family members, and feeling that their exposure to cholera may tarnish their social standing in the long term. These lived experiences of cholera are consistent with existing, but limited, literature from other settings where cholera outbreaks occur during complex crises or within fragile states and among populations with high levels of poverty [ 40 , 41 ]. Our study found that exposure to cholera decreased the household’s access to food and made it hard to prioritise handwashing due to a reduced ability to access water purchase soap in the wake of their illness.…”
Section: Discussionsupporting
confidence: 82%
“…We also contribute to work in economics, political science and social epidemiology on the role of redistributive institutions and domestic policy in managing the effects of epidemics of infectious disease (Adda, 2016;Chigudu, 2020Chigudu, , 2019Farmer, 1996Farmer, , 2001Geoffard and Philipson, 1996;Krieger, 2001;Leach, Scoones, and Stirling, 2010;Philipson, 1999;Youde, 2017;Copeland et al, 2013). We expand these literatures by providing quantitative estimates of the role of global and domestic redistributive institutions in managing the impacts of epidemics of infectious disease.…”
Section: Shocksmentioning
confidence: 98%
“…As Didier Fassin writes of South African rumours about medical experiments on the population, these circulated the way they did because ‘plots were actually conceived, horrifying stories were partially disclosed and circulated’ (2008: 324). And as Simukai Chigudu compellingly argues in the case of a cholera outbreak in Zimbabwe in 2008/9, the notion that the government would poison water supplies with cholera was convincing for many, precisely because it resonated with people's substantive experiences of citizenship: houses demolished, aid withheld, opposition supporters crushed, and the overall uneven provision of public services (Chigudu 2019: 420, 428). For most of the last sixty years of Angolan history, political violence – including by the government – was a brutal reality and Angolans had every reason to distrust official explanations.…”
Section: Suspecting the Statementioning
confidence: 99%